Realistic Repercussions of the Lack of Contractual Will in the Compulsory Motor Insurance Policy and Solutions to the Legislative Will - Al Tarawneh, Abdallah Imhammad Khalaf (Dirasat: Shari'a and Law Sciences, 2025)
Objectives: The study aims to clarify the legal meaning of the compulsory insurance policy for vehicles and the limits of the role of the will in determining its contractual content. It seeks to determine the relationship between the insolvency of the insurance company, insurance control, and the restriction of the freedom of both parties in the compulsory insurance policy. Additionally, it aims to identify the most important guarantees that ensure the rights of the insured in the event of the insolvency of the insurance company. Methods: The study adopted the descriptive-analytical approach, analyzing legal texts related to insurance business in Jordanian legislation. It examines their adequacy in addressing problems arising from compulsory vehicle insurance and their impact on the freedom of the parties in determining the contractual content of the unified insurance policy. Results: The study concluded that the will of both parties to a compulsory motor vehicle insurance policy lacks the ability to determine its content and choose which party should make the selection. This negatively impacts the insurance company’s ability to carry out its work and fulfill obligations when it becomes insolvent, affecting the rights of the insured and the beneficiaries. Conclusions: The study recommends that the insurance business regulator amend the compulsory insurance system for vehicles, allowing for a margin of contractual freedom in determining the contractual content of the compulsory insurance policy, and activating the text of Article 79 of the Insurance Business Law.